The Conceptualisation of Impoliteness in Russian and English - Margarita L Kharlova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2014)
The article analyses the concept of “impoliteness” in Russian and English. On the basis of the material taken from various explanatory dictionaries and corpus data the article presents a comparative analysis of the Russian and English words for “impolite”, which provides a means of identifying cultural implications of the concept in the corresponding linguaculture. The analysis of the definitions, synonyms, and usages of the words for “impolite” in the languages under study in the lexicographical sources, in the National Corpus of the Russian Language, and the Corpus of Contemporary American English allow us to conclude that impoliteness possesses different linguocultural content. Both in the Russian and English languages it is connected with breaching politeness norms. Additionally, impoliteness in the Russian language and culture correspondently is associated with the notions of propriety and deference, and has moral and ethical ground, whereas in the English language and culture impoliteness is based on the external non-demonstration of etiquette politeness, respect, tack and good manners. Thus, the study of the semantic content of the linguistic signs naming the concept of impoliteness makes it possible to further turn to the category of impoliteness that reflects the experience of impolite interaction. The main research methods used in the study are definitional analysis, corpus data analysis, descriptive and comparative methods.